2016
DOI: 10.3389/fpls.2016.01524
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis and Ultrastructure Observation Reveal that Hawthorn Fruit Softening Is due to Cellulose/Hemicellulose Degradation

Abstract: Softening, a common phenomenon in many fruits, is a well coordinated and genetically determined process. However, the process of flesh softening during ripening has rarely been described in hawthorn. In this study, we found that ‘Ruanrou Shanlihong 3 Hao’ fruits became softer during ripening, whereas ‘Qiu JinXing’ fruits remained hard. At late developmental stages, the firmness of ‘Ruanrou Shanlihong 3 Hao’ fruits rapidly declined, and that of ‘Qiu JinXing’ fruits remained essentially unchanged. According to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 66 publications
(63 reference statements)
0
27
0
Order By: Relevance
“…Due to ripening and senescence after harvest, kiwifruit quality will be seriously affected, and the storage period will be shortened because of membrane deterioration, cell‐wall degradation, cell‐structure modification, and cell death . Cell‐wall degradation is associated with cell‐wall hydrolases, including pectinesterase (PME), polygalacturonase (PG), β ‐gal, α ‐arabinofuranosidase ( α ‐L‐af), xyloglucan endotransglycosylase / hydrolase (XTH), and cellulase . Pectinesterase catalyzes the demethylesterification of cell‐wall polygalacturonans, which promotes the hydrolysis of polygalacturonic acid by PG .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to ripening and senescence after harvest, kiwifruit quality will be seriously affected, and the storage period will be shortened because of membrane deterioration, cell‐wall degradation, cell‐structure modification, and cell death . Cell‐wall degradation is associated with cell‐wall hydrolases, including pectinesterase (PME), polygalacturonase (PG), β ‐gal, α ‐arabinofuranosidase ( α ‐L‐af), xyloglucan endotransglycosylase / hydrolase (XTH), and cellulase . Pectinesterase catalyzes the demethylesterification of cell‐wall polygalacturonans, which promotes the hydrolysis of polygalacturonic acid by PG .…”
Section: Introductionmentioning
confidence: 99%
“…6 Cell-wall degradation is associated with cell-wall hydrolases, including pectinesterase (PME), 7 polygalacturonase (PG), 8,9 ⊎-gal, 10 ⊍-arabinofuranosidase (⊍-L-af), 11,12 xyloglucan endotransglycosylase / hydrolase (XTH), 13,14 and cellulase. 15 Pectinesterase catalyzes the demethylesterification of cell-wall polygalacturonans, 16 which promotes the hydrolysis of polygalacturonic acid by PG. 17 ⊎-Gal is hydrolyzed to pectin and hemicellulose, as a pectin-debranching enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…However, VvXTH and VvEXP were significantly upregulated in ‘Muscat Hamburg’ compared with ‘Red Globe’. In addition, the transcript encoding Vvβ-GAL showed a similar gene expression pattern as that of VvEXP , suggesting that Vvβ-GAL may be related to berry firmness, as these genes are involved in fruit softening [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the previous research, an RNA-Seq experiment was conducted using Illumina HiSeq 2500 by Xu and Dong [43]. The accession number was PRJNA339788.…”
Section: Est-ssr Mining From Rna-seq and Primer Designmentioning
confidence: 99%
“…Yang et al [42] used RNA-seq analysis identified numerous candidate genes involved in the hawthorn (C. pinnatifida) biosynthesis of polyphenolic compounds. Xu et al [43] used RNA-Seq analysis to study soft and hard flesh textures in hawthorn (C. pinnatifida) fruits. All these research studies aided the studies on the development of expressed sequence tag SSRs (EST-SSRs), which are located in the flanking coding region and identified from transcribed RNA sequence, while the genomic SSRs (g-SSRs) are identified from random genomic sequences [44].…”
Section: Introductionmentioning
confidence: 99%